Effect of Stretchable Circuit Deformation on Its Electrical Performance for Automotive Lighting Application / M. F. M. Sharif...[et al.] - M. F., M. Sharif; A., A. Saad; F. C., An; M. Y., T. Ali; Z., Samsudin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The purpose of this paper is to investigate the effect of the stretchable circuit deformation during a thermoforming process on its electrical performance for automotive lighting. The thermoforming process was carried out using a mould that was developed based on commercially available automotive lighting product. The circuit was printed on a 2-D thermoplastic substrate using screen printing technique before transformed into 3-D shape through the thermoforming process followed by LEDs assembly. The quality of the product were characterised before and after the thermoforming process by measuring the resistance and resistivity of the circuit. Voltage drops and luminance each of the LEDs resulted from the deformation of the circuit were compared with the current automotive lighting product. The study shows that the new design with stretchable material has similar performance with previous design in terms of electrical performance. These findings will encourage further development of new design of automotive lighting in the future.